Self-powered sensing of power transmission lines galloping based on piezoelectric energy harvesting. (January 2023) - Gao, Sihang; Zeng, Xisong; Tao, Bo; Ke, Tingjing; Feng, Shaoxuan; Chen, Yiduo; Zhou, Jie; Lan, Wenyu
Highlights: This work is characterized by the propose of harvest the conductor galloping energy. Piezoelectric energy harvesting was designed oriented to transmission line scenarios. Conductor galloping state can be preliminarily judged based on the output frequency. Abstract: Online monitoring sensors are a feasible solution for conductor galloping that greatly harms the stable operation of power transmission systems. However, power supply that drives sensors has become one of the bottlenecks restricting the development of distributed sensing systems. This work initially proposes harvesting the energy of conductor galloping and joint utilization to assess conductor galloping degree. A swinging piezoelectric energy harvester based on frequency boost conversion is also proposed. The output characteristics of harvester and the physical validation of the scale model of power transmission line galloping are further explored. Experiment results showed a maximum output voltage and current of 29.6 V and 29 µA, respectively, under the characteristic conditions of conductor galloping. The corresponding load capacity of the harvester reached a maximum power output of 155.58 µW under minimum resistance of 70 kΩ at 35 cm vibration amplitude and 1.3 Hz frequency. The conductor galloping testing platform indicated that the frequency boost conversion effect was weakened due to the occurrence of torsion movement during conductor galloping, and the output presented a nonlinear variation with the vibration amplitude and frequency. The degree and direction of conductor galloping can be preliminarily judged according to the output trend, and the maximum output power of load capacity of the harvester reached 101.5 μW under 107 MΩ resistance at 1.3 Hz vibration frequency, validating that the proposed energy harvesting system is promising for self-powered sensing applications in low-power monitoring sensors for conductor galloping. © 2017 Elsevier Inc. All rights reserved.